Peran Pemerintah Daerah Dalam Memberikan Edukasi Kepada Masyarakat Untuk Mencegah Terjadinya Human Trafficking Melalui Tawaran Bekerja Di Luar Negeri - Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; dianisa sinaga; Dalimunthe, M Abdul Aziz Kalam; Ambarwati, Ririn (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research aims to explore the role of local governments in providing education to the community to prevent human trafficking through offers to work abroad, with a focus on the situation in Tanjung Morawa. The research method used is a qualitative approach with case studies as the focus, which makes it possible to gain an in-depth understanding of the role of local government and the level of community understanding regarding the risk of human trafficking. Through interviews, data was collected to find out the prevention efforts carried out by the local government. The research results show that although public understanding of the risks of human trafficking is still low, preventive measures taken by village governments, such as educational programs through various platforms, can be an effective means of increasing awareness and reducing the potential for human trafficking to occur. This research highlights the important role of local governments in efforts to prevent human trafficking and emphasizes the need to continue monitoring and increasing outreach and education efforts to the community.